Research progress on FOXM1 in ovarian cancer diagnosis and therapeutics - Tan, Xiao-Qing; Guo, Ai-Ying; Zheng, Li-Fei; Xiong, Jun (Frontiers in Oncology, 2025)
Ovarian cancer (OC) is the leading cause of cancer-related death among women, presenting a significant threat to their lives and health. Early-stage OC often lacks distinctive clinical symptoms, leading to most patients being diagnosed at advanced stages. Current treatment strategies primarily involve a combination of surgical resection and chemotherapy, but the therapeutic outcomes are limited, and prognosis remains poor. Therefore, there is a critical need to understand the pathogenesis of OC, identify biomarkers for early diagnosis and prognosis, and discover new therapeutic targets. Forkhead box M1 (FOXM1), recognized as a pro-oncogenic transcription factor (TF), is notably overexpressed in various malignancies, including OC. Research indicates that increased levels of FOXM1 correlate significantly with OC’s aggressive behaviors such as proliferation, invasion, migration, epithelial-mesenchymal transition (EMT), and resistance to chemotherapy. These observations suggest that FOXM1 could potentially function as both a biomarker and a therapeutic target, facilitating the early detection and treatment of OC.